Mobile Learning In Class Learning System (Mobile Learning Dalam Pembelajaran Sistem Kelas) - Asaduddin Luqman (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Activities of e-learning tend to use mobile devices to access online learning materials so that it emerges a new definition called mobile learning (m-learning). M-learning is part of the e-learning, as a new stage of progress of e-learning. M-learning focused on learning experience across spatial, temporal, conceptual, and involves interaction among them using mobile devices. Interactions between components of learning with mobile technologies that are integrated into the pedagogical process continue to grow as development of information technology. At this time the mobile learning is on demands as an innovation in learning. Learning with mobile technology can be used as a supplement to support classroom learning system. The aims for learners is they could learn from various sources, allowing for learning anywhere and anytime so it can use time efficiently, and encourage the development of skills that can be practiced outside the classroom.